MULTICRITERIA DECISION MAKING USING PYTHAGOREAN FUZZY SET - J.Jayaraj; R.Raghu; R.Ezhilarasi (Utilitas Mathematica, 2025)
Decision‐making in uncertain and imprecise environments often requires robust mathematical frame‐works to evaluate multiple alternatives against diverse criteria.